Ammonium uptake and growth kinetics of pseudomonas putida PGA1 - Annuar, Mohamad Suffian Mohamad; Tan, Irene Kit Ping; Ibrahim, Shaliza; Ramachandran, K.B. (Malaysian Society for Molecular Biology and Biotechnology, 2006)
Ammonium uptake kinetics of low specific growth rate cultures of Pseudomonas putida PGA1, a gram negative fluorescent pseudomonad, which is an important producer of poly(3-hydroxyalkanoates) (PHA) molecules, were studied. The ammonium uptake follows a first-order kinetics model, indicating that the micro-organism’s specific uptake rate of ammonium and its growth would increase as the ammonium ion concentrations become higher. Optimal ammonium uptake and growth rates were observed at 0.1 gL-1 ammonium ion in aqueous medium. It also indicated that the ammonium transport mechanism is probably inducible by ammonium concentration. The limit of ammonium ion level increase before cells stop growing completely is given by the substrate inhibition constant, Ki which equals to 1.2 gL-1 ammonium ion concentration.